2013
DOI: 10.3390/ijms14034400
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Initiation Complex Assembly within the Wild-Strain of Coxsackievirus B3 and Live-Attenuated Sabin3-like IRESes during the Initiation of Translation

Abstract: Coxsackievirus B3 (CVB3) is an enterovirus of the family of Picornaviridae. The Group B coxsackieviruses include six serotypes (B1 to B6) that cause a variety of human diseases, including myocarditis, meningitis, and diabetes. Among the group B, the B3 strain is mostly studied for its cardiovirulence and its ability to cause acute and persistent infections. Translation initiation of CVB3 RNA has been shown to be mediated by a highly ordered structure of the 5′-untranslated region (5′UTR), which harbors an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 87 publications
(95 reference statements)
1
7
0
Order By: Relevance
“…Interestingly, the mutant RNA showed a reduced protein-binding profile compared to the wild-type domain V. A number of proteins binding to the domain V were identified: p220 (eIF4G), p116 (eIF3) and p80 (eIF4B). Filter-binding assays showed a better binding affinity of eIF3, eIF4G and eIF4B to the wild-type CVB3 domain V. These results perfectly correlate with the impaired protein-binding and the reduced translation efficiency previously reported with the Sabin3-like construct [ 41 - 44 ].…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations
“…Interestingly, the mutant RNA showed a reduced protein-binding profile compared to the wild-type domain V. A number of proteins binding to the domain V were identified: p220 (eIF4G), p116 (eIF3) and p80 (eIF4B). Filter-binding assays showed a better binding affinity of eIF3, eIF4G and eIF4B to the wild-type CVB3 domain V. These results perfectly correlate with the impaired protein-binding and the reduced translation efficiency previously reported with the Sabin3-like construct [ 41 - 44 ].…”
Section: Introductionsupporting
confidence: 84%
“…According to our previously published data [ 43 , 44 ], we suspected that the Sabin3-like mutation would impair the binding of cellular protein factors to the viral RNA that mediate the association of the ribosomal 40S subunit within the CVB3 IRES, and particularly, to the domain V. Four polypeptides of 220, 116, 80 and 57 kDa suspected as eIF4G, eIF3b, eIF4B and PTB, respectively bound to the CVB3 IRES RNA in the presence of BHK-21 cell extract and a reduction in the RNA-protein binding profile for the mutant RNA compared to the wild-type IRES were reported [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, Ben M'hadheb- Gharbi et al ( , 2007 constructed equivalent attenuating mutations into the genomic context of CVB3 strains and reported that the Sabin3-like mutation (U 473 →C) led to a serious impairment of the translation efficiency (Souii et al 2013), a reduction of the virus titer and a destabilization of the secondary structure of the IRES. They also demonstrated that the inoculation, by oral route, of Swiss mice within the Sabin3-like strain did not show any histological alterations in heart tissue when compared to hearts of mice infected with the wild-CVB3 strain (Souii et al 2013).…”
Section: Introductionmentioning
confidence: 99%